2002
DOI: 10.1136/ard.61.4.335
|View full text |Cite
|
Sign up to set email alerts
|

Which patients stop working because of rheumatoid arthritis? Results of five years' follow up in 732 patients from the Early RA Study (ERAS)

Abstract: Objectives: To assess the occurrence and prognostic factors for the ability to maintain paid work in patients with rheumatoid arthritis (RA). Setting: Inception cohort of patients with RA recruited from rheumatology departments in nine NHS Hospital Trusts in England. Patients: All consecutive patients with RA of less than two years' duration, before any second line (disease modifying) drug treatment, and followed up for five years. Methods: Clinical, laboratory, and radiological assessments, and all treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
165
8
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(189 citation statements)
references
References 21 publications
(27 reference statements)
11
165
8
3
Order By: Relevance
“…For example, we also found that work autonomy, functional status, pain, and social support were linked to outcomes (3)(4)(5)(6)(7)(8)11,13). However, unlike other studies, we did not find that depressive symptoms were associated with work outcomes (12), possibly because the prevalence of depressive symptoms in our samples was low.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…For example, we also found that work autonomy, functional status, pain, and social support were linked to outcomes (3)(4)(5)(6)(7)(8)11,13). However, unlike other studies, we did not find that depressive symptoms were associated with work outcomes (12), possibly because the prevalence of depressive symptoms in our samples was low.…”
Section: Discussioncontrasting
confidence: 79%
“…Job loss also has been associated with greater disease severity measured by physical examination, laboratory tests, radiographs, functional status, and symptoms such as pain and fatigue (6 -9,13-16). As expected, more physical requirements, such as lifting and precision writing, and less work autonomy, such as less control over the daily workload, pace of work, and work hours, are also related to job loss (3,(7)(8)(9)17).…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The substantial impact of rheumatoid arthritis (RA) on work disability and job loss has recently received considerable attention (1,2) and represents a significant economic burden (3)(4)(5). Recent developments in therapies targeted against tumor necrosis factor (TNF) have changed the approach to RA treatment by rapidly controlling the disease, particularly in early disease (6,7) when the opportunity to prevent structural damage is critical.…”
Section: Introductionmentioning
confidence: 99%
“…Even early in the disease process this is common despite early pharmacological interventions with disease-modifying anti-rheumatic drugs (DMARD) [1][2][3][4][5]. Work disability in RA is dependent on many factors, such as disease activity, activity limitations and environmental demands [6][7][8]. Also, from qualitative approaches, it is known that patients with RA experience that participation in work is influenced by symptoms such as morning stiffness, fatigue and pain as well as environmental factors such as support from employers and colleagues [9].…”
Section: Introductionmentioning
confidence: 99%